(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article, the life path, creativity and the study of the son of Zakirjon Kholmuhammad, who wrote poems under the pseudonym of Furqat, a major representative of Uzbek classic literature, during his earlier life, as well as now. In the study of the writer’s life and work, his memoir ``Condition of the Khokhand poet Zakirjon Furqat, his own writing’’ is a valuable source. Below is also a reference to this work.